CURRICULUM IMPLEMENTATION IN SPECIAL CONDITIONS BASED ON TEACHERS WORKING GROUPS IN PRIMARY SCHOOLS IN WEST SUMBA - Dagha, Yakobus Umbu (Postgraduate School, Universitas Nusa Cendana, 2024)
Abstract: The Covid-19 pandemic has had an impact on all sectors. In the education sector, the impact is that learning does not take place directly because teachers and students do not meet face-to-face in class. The research aims to identify and describe a special curriculum based on teacher working groups in elementary schools in West Sumba. Type of qualitative research. Data collection methods are observation, interviews, and documentation. Data analysis uses descriptive data, namely: reducing data, analyzing data, and drawing conclusions. The research results show that the implementation of a special curriculum based on teacher working groups in six elementary schools in West Sumba refers to simplified basic and core competencies. Teachers create learning tools guided by a special curriculum, learning is carried out online and offline, and create gathering points. The training system is based on class level, where each class teacher from each school gathers to carry out activities based on the class level they teach. Supporting factors are adequate facilities and infrastructure while inhibiting factors are that not all teachers have electronic devices, unstable internet networks, and limited access to technology. Keywords: Special Curriculum and Teacher Working Group